Serum IL-38 Level Was Associated with Incidence of MACE in the STEMI Patients - Lu C; Zhou F; Xian H; Sun S; Yue J; Zhang Y; Zhao Q; Luo X; Li Y (International Journal of General Medicine, 2023)
Chengbo Lu,1,* Fanghui Zhou,2,* Huimin Xian,3,* Siyuan Sun,4 Jingkun Yue,4 Ying Zhang,5 Qi Zhao,6 Xing Luo,3 Yang Li7 1Department of Cardiology, 1st Affiliated Hospital of Jiamusi University, Jiamusi, Heilongjiang, People’s Republic of China; 2Department of Hematology, 2nd Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 3Department of Cardiology, 2nd Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 4Department of Cardiology, People’s Hospital of Taihe County, Taihe, Anhui, People’s Republic of China; 5Department of Gynaecology and Obstetrics, 1st Affiliated Hospital of Jiamusi University, Jiamusi, Heilongjiang, People’s Republic of China; 6Department of Cardiology, 1st Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 7Department of Cardiology, 4th Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xing Luo; Yang Li, Email luoxing321@163.com; jacksonbiotechlab@gmail.comBackground: The relationship between serum IL-38 and major adverse cardiovascular events (MACE) in patients with ST elevation myocardial infarction (STEMI) remains unclear.Methods: In the present study, 589 STEMI patients were included, the serum level of IL-38 was measured. The median follow-up time was 720 days, the STEMI patients were divided into high IL-38 (IL-38> 6.49ng/mL) and low IL-38 groups (IL-38≤ 6.49ng/mL) to compare the probability of MACE.Results: Plasma IL-38 levels were significantly lower in STEMI patients than in SAP patients (4.0± 2.2 vs 6.9± 3.2 ng/mL, P < 0.001). Ninety-three STEMI patients met the defined MACE study endpoint. The incidence of MACE was significantly lower in patients with high IL-38 group than in patients with low IL-38 group (7.8% vs 23.7%, P < 0.001). Low plasma IL-38 levels were independently associated with the occurrence of MACE (OR = 0.90, P < 0.001).Conclusion: We get a conclusion that low plasma levels of IL-38 are independently associated with the occurrence of MACE.Graphical Abstract: Keywords: inflammatory response, SAP, IL-38, STEMI, MACE